ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA TIPE HOTS BERBASIS LANGKAH POLYA - Charomah Sri Setianing Rahayu; Sri Sutarni (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
This study was aimed at finding two objectives, there were the description of student difficulties in solving HOTS type math problems based on polya steps and the factors that caused students difficulties in solving polya step-based HOTS math problems. This study experienced by high school students in class X in Klaten Regency. This study was descriptive research with a qualitative approach. The subjects of this study were 24 class X high school students in Klaten Regency. This study used observation data collection techniques, written tests, interviews, and documentation. The results showed that difficulty to understand the problem (5.47%), difficulty to plans (12.80%), difficulty to implement the plan (27.13%), and difficulty to check again (54.59%). The factors of high school students' difficulties in solving HOTS type math problems based on polya steps came from internal factors and external factors. The internal factors were low students' interest in mathematics, low students' motivation, and bad students' attitudes in dealing with math problems. The external factors were experience solving HOTS questions, inattention of family environment and unpleasant of home situation, the school environment, such as inadequate facilities, and the community environment that drain student times.